Characterization of the Role of a Non-GPCR Membrane-Bound CFEM Protein in the Pathogenicity and Germination of Botrytis cinerea - Gulab Chand Arya; Dhruv Aditya Srivastava; Eswari P. J. Pandaranayaka; Ekaterina Manasherova; Dov Bernard Prusky; Yigal Elad; Omer Frenkel; Hay Dvir; Arye Harel (Microorganisms, 2020)
The necrotrophic fungus Botrytis cinerea, is considered a major cause of postharvest losses in a wide range of crops. The common fungal extracellular membrane protein (CFEM), containing a conserved eight-cysteine pattern, was found exclusively in fungi. Previous studies in phytopathogenic fungi have demonstrated the role of membrane-bound and secreted CFEM-containing proteins in different aspects of fungal virulence. However, non-G protein-coupled receptor (non-GPCR) membrane CFEM proteins have not been studied yet in phytopathogenic fungi. In the present study, we have identified a non-GPCR membrane-bound CFEM-containing protein, Bcin07g03260, in the B. cinerea genome, and generated deletion mutants, ΔCFEM-Bcin07g03260, to study its potential role in physiology and virulence. Three independent ΔCFEM-Bcin07g03260 mutants showed significantly reduced progression of a necrotic lesion on tomato (Solanum lycopersicum) leaves. Further analysis of the mutants revealed significant reduction (approximately 20–30%) in conidial germination and consequent germ tube elongation compared with the WT. Our data complements a previous study of secreted ΔCFEM1 mutants of B. cinerea that showed reduced progression of necrotic lesions on leaves, without effect on germination. Considering various functions identified for CFEM proteins in fungal virulence, our work illustrates a potential new role for a non-GPCR membrane CFEM in pathogenic fungi to control virulence in the fungus B. cinerea.